Studi Distribusi Glukosa Transporter 4 pada Otot Skelet Ayam Kedu Cemani - Teguh Budipitojo; Ariana -; Tri Wahyu Pangestiningsih; Hery Wijayanto; Dwi Liliek Kusindarta; Dewi Kania Musana (Jurnal Sain Veteriner, 2017)
Glucose transporter (GLUT 4) is glucose transporter protein regulated by insulin, found in adipose tissue and striated muscle (skeletal and cardiac muscle). Kedu cemani chicken is one of Indonesia endemic animal, found in Kedu, Temanggung regency, Central Java. This study was required to complete microscopic documentation of  Indonesia’s native biodiversity. The objective of this study was to clarify GLUT 4 distribution in skeletal muscle fibers of kedu cemani chicken by using avidin-biotin-peroxidase complex (ABC) immunohistochemistry method. This study was conducted by using pectorales major, biceps brachii, and biceps femoris muscle tissue from 5 kedu cemani chicken. The result showed that GLUT 4 immunoreactivity were detected in sarcolemma and myofibrils component of pectorales major, biceps brachii, and biceps femoris muscle tissue. Intensity of GLUT 4 immunorectivites increased from weak intensity in pectorales major muscle tissue, moderate intensity in biceps brachii muscle tissue, then strong intensity in biceps femoris muscle tissue. This result might motivate to further exploration about the other kedu cemani chicken specific features to complete microscopic  documentation of  Indonesia’s native biodiversity.